Pemanfaatan Limbah Polyethylene pada Campuran Lapis Tipis Aspal Beton - Agus Juhara; Hanafi Hanafi; Rifqi Adhyaksa P; Novan Selamet Nugraha R (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2023)
Flexible pavement is a road pavement that uses asphalt as a binder. Asphalt mixture performance needs to be improved by modifying using admixture material to improve its durability and resistance to plastic deformation. To increase the performance of asphalt mixtures, one of the alternatives is to utilize Polyethylene (PE) plastic waste. Hot Rolled Sheet (HRS) has a relatively high asphalt content compared to other types of mixtures because of is waterproof. This study was carried out using the dry method, Polyethylene (PE) plastic waste was added to the aggregate and hot asphalt mixture at the temperature of the mixture. Variations in the content of Polyethylene (PE) plastic waste added are 3%, 3.5%, and 4% by weight of asphalt. The characteristics of the asphalt mixture were the test results showed an increase in stability of 10 - 20% and the melting value was at 3 - 4mm. The residual strength index value shows that the addition of Polyethylene (PE) plastic waste can increase the resistance to damage by a percentage of 0.55% compared to without the addition of Polyethylene (PE) plastic waste. The level of addition of Polyethylene (PE) plastic waste is in the range of 3.5-3.9%.